Class, violence and citizenship in the Arab uprisings: assessing deeper forms of transition - Challand, Benoit (Historein, 2015)
The article connects the literature on transitology with a comparative analyses of the Arab uprisings (also known as the “Arab Spring”). These uprisings should not only be assessed against the backdrop of institutional changes (elections, the writing of new constitutions, the emergence of party systems, etc.). Rather, we need to consider the revolts as a set of historical events sharing a common aspiration towards a renewed and reactivated sense of citizenship from below, that is, from spontaneous forms of civil society, in conjunction with innervated trade union movements, and the emergence of new coalitions pushing for a more participatory politics. The article concentrates on two features of citizenship: the role of the middle class in fighting for larger political enfranchisement and the attempts by the sovereign people to reappropriate the legitimate means of violence.